Phase-Based 3-D Source Localization Using 1-b Quantized Measurements Under Uniform Circular Array - Chen, Xin; Liu, Zhen; Liu, Tianpeng; Peng, Bo; Su, Xiaolong; Li, Xiang (IEEE sensors letters, 2020)
1-b quantization has become an important topic in modern signal processing. In this letter, we consider the problem of 3-D source localization by combining 1-b quantized measurements and the phase-based algorithm under a uniform circular array. With analysis, unquantized and 1-b quantized cross-correlation coefficient can be approximated by the arcsine law and Taylor series approximation under sufficiently low signal-to-noise ratio (SNR). Even at high SNR levels, the approximated error only slightly affects source localization. Therefore, under 1-b quantized measurements, the phase-based algorithm can be straightforwardly applied to source's 3-D localization without extra preprocessing. Numerical examples demonstrate the theoretical analysis.